Unplanned Surgical Incisions in Bone and Soft Tissue Tumor Biopsy: Are we up to the mark? (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the frequency of inappropriately placed biopsy incision in patients with bone and soft tissue tumors.Methods: This retrospective cross sectional study was conducted in Orthopaedic and Oncology unit Rehman Medical Institute. The records of all the patients with bone and soft tissue tumors presented during time period extending from 23rd May 2017 to 23rd June 2022 were reviewed. Appropriateness of the surgical margins and surgical scars were assessed after complete staging studies. During subsequent surgery, if required, the need for complex reconstructive procedures in the form of local or free flaps or skin grafting was assessed along with ablative surgery due to the wrongly placed surgical incisions.Results: The records of 451 patients were studied out of which 184(40.79%) patients had biopsies performed in the author's institution. Of the remaining patients 77(28.83%) had wrong or inappropriately based surgical incisions with most of those were in soft tissue tumor cases (75.32%). Few (10.38%, n=8) of the inappropriately based incision cases had to undergo amputation while the rest had their limb salvaged.Conclusion: The frequency of inappropriately placed biopsy incision in patients with bone and soft tissue tumors was high. We are not up to the mark. We recommend further training for musculoskeletal (MSK) oncology cases performed only in referral units to optimize outcome.